Mapping Benthic Habitat Distribution and Coral Reef Health Index in Ternate Island and Tidore Island, North Maluku - Patty, Simon I.; Souhoka, Jemmy; Makatipu, Petrus C.; Rizqi, Marenda Pandu (Jurnal Ilmiah Platax, 2024)
Coral reefs are underwater marine organisms whose coverage can be identified using remote sensing technology utilizing satellite imagery. The benthic habitats classification and coral reef health index analysis were carried out on the Ternate and Tidore islands in June 2021. This study aims to map the distribution of benthic habitat as well as calculate the value of the coral reef health index. The processing of satellite imagery data from Landsat 8, using ENVI 5.3 and ArcGIS 10.1 software. The "depth invariant index" algorithm is used in the image sharpening process (Lyzenga, 1981). The maximum likelihood classification technique is used to identify substrate type, with a confusion matrix used to test its accuracy. The coral reef health index assessment is based on the condition of live coral cover, resilience level, and reef fish biomass. The results from water column image classification showed that there were four classes of habitat, i.e. coral, seagrass, sand, and rubble with an overall accuracy value of 85.86% and kappa coefficient of 0.80605. The total area of classified coral reefs is 1152.85 hectares. The coral reef health index values ranged from 2 to 8 with an average of 5, which translates to a moderate percentage of live coral cover, high resilience, and low fish biomass. Keywords: coral reefs, benthic habitat, health index, Landsat 8 images.   Abstrak Terumbu karang merupakan objek tutupan bawah air laut yang dapat diidentifikasi menggunakan teknologi penginderaan jauh yakni memanfaatkan citra satelit. Klasifikasi habitat bentik dan analisis indeks kesehatan terumbu karang telah dilakukan di pulau Ternate dan pulau Tidore pada bulan Juni 2021. Penelitian ini bertujuan untuk memetakan sebaran habitat bentik serta mengetahui nilai indeks kesehatan terumbu karang. Pengolahan data citra Landsat 8 dengan perangkat lunak ENVI 5.3 dan ArcGIS 10.1. Proses penajaman citra menggunakan algoritma “depth invariant index” (Lyzenga, 1981). Teknik klasifikasi maximum likelihood digunakan untuk identifikasi objek dasar perairan dan uji akurasi menggunakan confusion matrix. Penilaian indeks kesehatan terumbu karang berdasarkan kondisi tutupan karang hidup, tingkat resiliensi dan biomassa ikan karang. Hasil klasifikasi citra kolom air mendapatkan empat kelas habitat yaitu karang, lamun, pasir dan pecahan karang mati (rubble) dengan nilai akurasi keseluruhan sebesar 85,86 % dan koefisien kappa sebesar 0,80605. Total luasan area terumbu karang hasil klasifikasi adalah 1152,85 ha. Nilai indeks kesehatan terumbu karang berkisar antara 2 sampai 8, dengan rata-rata 5 yang menggambarkan persentase tutupan karang hidup sedang, tingkat resiliensi tinggi dan biomassa ikan rendah. Kata kunci: terumbu karang, habitat bentik, indeks kesehatan, citra Landsat 8.